Association of CD14‐260 polymorphisms, red‐complex periodontopathogens and gingival crevicular fluid cytokine levels with cyclosporine A‐induced gingival overgrowth in renal transplant patients. (31st August 2012) - Gong, Y.; Bi, W.; Cao, L.; Yang, Y.; Chen, J.; Yu, Y.
<x xml:space="preserve">Abstract</x> Backgroud and Objective Genetic factors may influence the colonization of pathogenic bacteria, therefore increasing the risk for the initiation and development of periodontal disease. The present study was carried out to investigate the association of CD14‐260 polymorphisms, subgingival microbiota, and gingival crevicular fluid (GCF) cytokine levels with cyclosporine A (CsA)‐induced gingival overgrowth (GO) in renal transplant patients. Material and Methods A total of 204 patients were dichotomized into two groups: 124 with GO and 80 without GO. The CD14‐260 polymorphisms were measured using an allele‐specific PCR method. The levels of periodontal pathogens were determined by real‐time PCR of subgingival samples. GCF levels of IL‐1β and sCD14 were detected by ELISA. Results The frequency of CD14‐260 genotype CT + TT was found to be similar in both groups. Patients with GO presented increased prevalence of Pg, Td, and Tf (red complex) and significantly higher levels of interleukin ‐1β than those without GO. Patients with GO carrying CT + TT genotypes were found to have higher frequencies of Pg, Td, and Tf than those carrying the CC genotype. Furthermore, in the presence of red complex, CT + TT genotypes were associated with higher interleukin ‐1β levels and severe GO. Multiple logistic regression analysis demonstrated that the severity of GO is not dependent on age, gender and pharmacological variables, being only associated with CD14‐260 genotype and red complex periodontopathogens. Conclusion No association between CD14‐260 polymorphisms and the prevalence of GO was revealed in renal transplant patients administered CsA. However, CD14‐260 CT + TT genotypes are associated with the prevalence of red complex periodontopathogens in patients with GO, and may thus play some role in the development of severe CsA‐induced GO.